2022
DOI: 10.14814/phy2.15372
|View full text |Cite
|
Sign up to set email alerts
|

Head hemodynamics and systemic responses during auditory stimulation

Abstract: The present study aims to analyze the systemic response to auditory stimulation by means of hemodynamic (cephalic and peripheral) and autonomic responses in a broad range of auditory intensities (70.9, 77.9, 84.5, 89.5, 94.5 dBA). This approach could help to understand the possible influence of the autonomic nervous system on the cephalic blood flow. Twenty‐five subjects were exposed to auditory stimulation while electrodermal activity (EDA), photoplethysmography (PPG), electrocardiogram, and functional near‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 122 publications
0
12
0
Order By: Relevance
“…The indirect nature of fNIRS and its limited depth coverage compared to fMRI, in addition to physiological factors in uencing cerebral hemodynamics, could explain the contradictory results found in the literature (Chen et al, 2015;Muñoz-Caracuel et al, 2021;Muñoz et al, 2022). Mulert (2010), suggests that, concerning the study of the hemodynamic response, it is possible that the synchronous activity of a small number of neurons may result in changes detectable by EEG, but that the hemodynamic changes generated are not enough to be detected by statistical tests, due to an insu cient change in baseline.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The indirect nature of fNIRS and its limited depth coverage compared to fMRI, in addition to physiological factors in uencing cerebral hemodynamics, could explain the contradictory results found in the literature (Chen et al, 2015;Muñoz-Caracuel et al, 2021;Muñoz et al, 2022). Mulert (2010), suggests that, concerning the study of the hemodynamic response, it is possible that the synchronous activity of a small number of neurons may result in changes detectable by EEG, but that the hemodynamic changes generated are not enough to be detected by statistical tests, due to an insu cient change in baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some conditions that stress the cerebral vasculature, could further decrease vascular distensibility, making it more di cult to nd the neurovascular coupling response between the electrical and hemodynamic signal. In humans, vascular responses to stress conditions have been most studied in autonomic and peripheral measurements, in which high intensities sounds seem to lead to a process of vasoconstriction analyzed by Pulse transit time (PTT) and/or Power spectral density (PSD) of the pulse signal, both vasoconstriction indicators (Franco et al, 2002;Galland et al, 2007, Muñoz et al, 2022. This issue could be especially relevant in studies in which the defense re ex could be masking the hemodynamic signals, as in the present report when high intensities are employed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, although embodied cognition is a relevant conceptual issue within the predictive coding framework (Allen & Friston, 2018;Seth & Friston, 2016), little empirical research has addressed this question in an integrative manner. Recent work from our group (Muñoz et al, 2022;Muñoz-Caracuel et al, 2021) has shown the complex relationship between the peripheral and central nervous system (CNS) during sensory information encoding and, to our knowledge, only a few studies have investigated these systemic responses using oddball paradigms. Lyytinen et al (1992) found that neither heart rate (HR) nor skin conductance response (SCR) seemed to correlate with the MMN elicitation, whereas elicitation of the P300 component would be associated with a higher SCR.…”
Section: Introductionmentioning
confidence: 99%